Polioencephalomalacia in Newborn Lamb - Nascimento, Karla Alvarenga; Ferreira Júnior, Jair Alves; Novais, Ernane de Paiva Ferreira; Perecmanis, Simone; Sant’Ana, Fabiano José Ferreira; Pedroso, Pedro Miguel Ocampos; Macêdo, Juliana Targino Silva Almeida (Acta Scientiae Veterinariae, 2020)
Background: Perinatal mortality in sheep is determined by death between 60 days of gestation and 28 days postpartum. The starvation / hypothermia complex was characterized by lambs that walked, but did not feed. Polioencephalomalacia (PEM) is a descriptive term that indicates the morphological diagnosis for necrosis with softening of the gray matter in the brain. There are no data available in the literature relating PEM to the starvation / hypoglycemia / hypothermia complex in small ruminants. Thus, the objective of this work is to report a case of polyioencephalomalacia related to the starvation / hypoglycemia / hypothermia and septicemia complex in a newborn sheep. Case: A 5-day-old sheep mixed race (Dorper x Santa Inês), female, 3.0 kg, from a rural property in the Federal District, was sent to the Veterinary Pathology Laboratory of the University of Brasilia, for a necropsy. Organ fragments were collected and fixed in a 10 % buffered formalin solution, routinely processed for histology and stained with Hematoxylin and Eosin (HE). Additionally, swabs from the meninges, eyeballs and navels were collected for bacteriology. The animal came from twin pregnancies and was weak since birth. With three days of life, it presented apathy, weakness, difficulty in breastfeeding, difficulty in walking, and decubitus in a self-auscultation position. After two days of evolution the lamb died. Macroscopically, eyeball opacity, omphalophlebitis and congested brain were observed. Microscopically in the frontal cortex, the leptomeninge was markedly thickened by a large number of neutrophils and, to a lesser extent, macrophages, lymphocytes and plasmocytes, associated with aggregates of free eosinophilic rods or in the cytoplasm of macrophages. In the underlying gray substance, the neurópilo was observed containing moderate amount of perineuronal vacuoles and distension of the perivascular space (perineuronal and perivascular edema), in addition to a large number of neurons with retracted and hypereosinophilic cytoplasm with the pycnotic and peripheral nucleus (neuronal necrosis). Moderate endothelial and astrocyte swelling was also observed. In the eyeball, they were seen in the anterior, posterior and vitreous chambers extending to the ciliary body, infiltrated by neutrophils, lymphocytes, plasmocytes and macrophages with a moderate amount of fibrin, which extended to the optic nerve papilla. In the vitreous chamber, a large number of free eosinophilic rods were found in the infiltrate and inside macrophages. The bulbar conjunctiva, the corneal limbus and the iridocorneal angle were slightly thickened by similar infiltrates. In the bacteriological examination of meninges, eyeballs and navels, pure Escherichia coli culture was isolated. Discussion: The diagnosis of PEM associated with meningitis and panuveitis in this study was based on clinical-pathological and microbiological findings. In small ruminants twin pregnancies occur more frequently, and it is common for puppies to be born weaker and not ingest colostrum properly, leading to a condition called failure in passive immunity transfer and thus developing some type of disease. Metabolic disorders that interfere with glycolysis and ATP production for neurons are among the causes of PEM, however there is little data in the literature relating PEM to the starvation / hypoglycemia / hypothermia complex. Another important factor related to inadequate colostrum intake and management is umbilical infections. Meningitis results from a septicemic manifestation of primary infection such as omphalophlebitis. The association of clinical and pathological data allowed the diagnosis of PEM associated with meningitis, which was confirmed by the isolation of Escherichia coli in pure culture.